SEMIOTIC ANALYSIS ON WAHYU KOKKANG’S CARTOONS IN CLEKIT JAWA POS - ZULKARNAIN, FUAD (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: semiotics, signs, code, icon, index, symbol, cartoon, clekit. Language and sign are connected since language is also the part of sign. The study of sign can be defined as Semiotics in linguistics. Semiotics is used to understand and interpreting every sign. The researcher conducted a study about semiotics in Wahyu Kokkang’s cartoon in Clekit Jawa Post which shows the interpretations of the cartoons that are published in one of the mostfamous newspapers in Indonesia. There are two problems to be solved in the study, namely (1) what are the Semiotics signs that can be found in Wahyu Kokkang’s cartoon in Clekit Jawa Post and (2) what are the interpretations of Semiotic signs that can be made in Wahyu Kokkang’s cartoon in Clekit Jawa Post.As the data of the study, the researcher took the signs from 7 cartoons that were published on Clekit Jawa Post. The researcher selected the political cartoons on March and April 2009 with the upcoming national election on April 2009 as the consideration of collecting the data. This study used qualitative approach in relation to the use of clear and systematic description about the phenomena being studied. The researcher had 3 steps in analyzing the data:(1) identifying the types of signs found in Clekit Jawa Post by using Pierce’s theory of sign,(2) interpreting the cartoons by combining all the signs employed, and (3) drawing conclusion of all findings that have been analyzed.This study reveals that all elements of sign which are icon, index, and symbol are applied in those seven cartoons. Overall, there are 22 icons, 9 indexes, and 14 symbols that are applied in the cartoons. This study also reveals that the cartoons are related to the reality that happened in the society, especially is related to politics.Furthermore, five out of seven cartoons are used to satirizea group of person or institution. On the other hand, two out of seven cartoons are used to remind some persons andan institution.The researcher suggests English Study Program students conduct a study about the signs and interpretations from other themes of cartoons such as cartoons related to education in order to enrich the interpretations of Clekit cartoons.